2002
DOI: 10.1177/109861110200500103
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Five Dimensions of Police Officer Stress: Looking More Deeply Into Organizational Settings for Sources of Police Stress

Abstract: Research on police officer stress has focused primarily on the rather atypical nature of police work and extent of adherence by law enforcement agencies across the nation to the Weberian bureaucratic form of organization and management practices. This study explores the effect of individual perceptions of work environment on male officer stress. Survey data from two large police departments in the northwestern United States are used in the analysis. The findings observed suggest that the levels of five dimensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
89
1
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(100 citation statements)
references
References 19 publications
4
89
1
6
Order By: Relevance
“…Black police officers were found to be more stressed than white officers (White et al 1985). In terms of gender, Pendergrass and Ostrove (1984) noted that female police personnel were found to report higher levels of physical stress than their male counterparts, and females are more likely to have higher workplace stress levels than males (Zhao et al 2002). However, it has been reported that female police officers did not differ significantly from their male counterparts in terms of job satisfaction (Dantzker and Kubin 1998) or workplace stress (Morash and Haarr 1995).…”
Section: Review Of the Literaturementioning
confidence: 90%
See 2 more Smart Citations
“…Black police officers were found to be more stressed than white officers (White et al 1985). In terms of gender, Pendergrass and Ostrove (1984) noted that female police personnel were found to report higher levels of physical stress than their male counterparts, and females are more likely to have higher workplace stress levels than males (Zhao et al 2002). However, it has been reported that female police officers did not differ significantly from their male counterparts in terms of job satisfaction (Dantzker and Kubin 1998) or workplace stress (Morash and Haarr 1995).…”
Section: Review Of the Literaturementioning
confidence: 90%
“…Of these four sources of stress for law enforcement officers, organizational stressors are considered to be the chief causes of stress (See Abdollahi 2001;Alexander 1999;Hart et al 1993Hart et al , 1995Laufersweiler 1995;Lord 2005;Morash and Haarr 1995;Patterson 1998;Stinchcomb 2004;Toch 2002). Lessening organizational stressors can serve to enhance departmental morale, productivity, and efficiency (Stevens 2005), and employee participation in decisionmaking has consistently been cited as a primary means for alleviating organizational causes of police stress (See Alexander 1999;Laufersweiler 1995;Morash and Haarr 1995;Morash et al 2006;Rodichok 1995;Tang and Hammontree 1992;Terry 1983;Violanti 1996;Zhao et al 2002).…”
Section: Review Of the Literaturementioning
confidence: 98%
See 1 more Smart Citation
“…Outras pesquisas realizadas nos Estados Unidos (Hasselt, Malcolm, Seaton, Perera & Sheehan, 2003;Violanti & Aron, 1995;Zhao, He & Lovrich, 2002) identificaram duas principais fontes estressoras: a natureza do trabalho policial e os fatores da organização. Assim, foram encontrados como fontes o perigo, os plantões e a apatia da população.…”
Section: Discussão E Conclusõesunclassified
“…Zhao, He, & Lovrich (2002) identified five dimensions of police stress, including depression, anxiety, obsessive/compulsive personalities, interpersonal sensitivity, and anger/hostility. In looking at several of these dimensions, research on depression in law enforcement shows that depression and anxiety among law enforcement officers are not uncommon (see Andrew, McCanlies, Burchfiel, Charles, Hartley, Fekedulegn, & Violanti , 2008;Hartley, Violanti, Fekedulegn, Andrew, & Burchfiel, 2007;Olson & Surrette , 2004).…”
Section: Literature Review On Law Enforcement Officer Health Wellnesmentioning
confidence: 99%